EZH2 mutational status predicts poor survival in myelofibrosis - Guglielmelli, Paola; Biamonte, Flavia; Score, Joannah; Hidalgo-Curtis, Claire; Cervantes, Francisco; Maffioli, Margherita; Fanelli, Tiziana; Ernst, Thomas; Winkelman, Nils; Jones, Amy V.; Zoi, Katerina; Reiter, Andreas; et al. (Blood, 2011)
We genotyped 370 subjects with primary myelofibrosis (PMF) and 148 with postpolycythemia vera/postessential thrombocythemia (PPV/PET) MF for mutations of EZH2. Mutational status at diagnosis was correlated with hematologic parameters, clinical manifestations, and outcome. A total of 25 different EZH2 mutations were detected in 5.9% of PMF, 1.2% of PPV-MF, and 9.4% of PET-MF patients; most were exonic heterozygous missense changes. EZH2 mutation coexisted with JAK2V617F or ASXL1 mutation in 12 of 29 (41.4%) and 6 of 27 (22.2%) evaluated patients; TET2 and CBL mutations were found in 2 and 1 patients, respectively. EZH2-mutated PMF patients had significantly higher leukocyte counts, blast-cell counts, and larger spleens at diagnosis, and most of them (52.6%) were in the high-risk International Prognostic Score System (IPSS) category. After a median follow-up of 39 months, 128 patients (25.9%) died, 81 (63.3%) because of leukemia. Leukemia-free survival (LFS) and overall survival (OS) were significantly reduced in EZH2-mutated PMF patients (P = .028 and P < .001, respectively); no such impact was seen for PPV/PET-MF patients, possibly due to the low number of mutated cases. In multivariate analysis, survival of PMF patients was predicted by IPSS high-risk category, a < 25% JAK2V617F allele burden, and EZH2 mutation status. We conclude that EZH2 mutations are independently associated with shorter survival in patients with PMF.